2005
DOI: 10.1002/lt.20390
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical experiment of auxiliary partial orthotopic liver transplantation as a curative treatment for hemophilia

Abstract: The cause of hemophilia is deficiency of coagulation factor VIII production in the liver, which can be cured by liver transplantation. Because the hepatic function of hemophilia patients is quite normal except for production of factor VIII, auxiliary partial orthotopic liver transplantation (APOLT) is beneficial in that patient survival is secured by preserving native liver even in the event of graft loss. However, it is not known whether the graft of APOLT would be enough to cure hemophilia. We evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
7
0
2
Order By: Relevance
“…This result is similar to that of a case report on use of a total liver graft [12]. A nonhuman animal model of APOLT for hemophilia also showed a similar level of factor VIII (w40%), which was observed for 7 weeks [13].…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to that of a case report on use of a total liver graft [12]. A nonhuman animal model of APOLT for hemophilia also showed a similar level of factor VIII (w40%), which was observed for 7 weeks [13].…”
Section: Discussionsupporting
confidence: 91%
“…Ko et al. [92] performed a study in a haemophilic dog with a FVIII activity <5% (The Queens University colony) in which they by auxiliary partial orthotopic liver transplantation (APOLT) were able to cure haemophilia. By transplantation of a liver lobe graft from a normal dog (FVIII activity >60%), the FVIII activity in the haemophilic dog was increased to 30% and sustained for an observation period of 6 weeks.…”
Section: Results Of Therapeutic Intervention In Animal Models Of Haemmentioning
confidence: 99%
“…Early transplant studies in these dogs showed that liver transplantation could correct the bleeder phenotype but that transplant of spleen or kidney did not have consistent or lasting positive effects . Beagles can also suffer from hemophilia A and have been used to show the efficacy of auxiliary partial orthotopic liver transplantation to treat hemophilia A . With the identification of the liver as the major source of FVIII, efforts focused on which cells in this organ were responsible for FVIII production.…”
Section: Fviii Is Produced By Lsecsmentioning
confidence: 99%